Efektifitas Kegiatan Pengerukan Sedimen Waduk Wonogiri Ditinjau Dari Nilai Ekonomi - Andriawati, Irene Dhian; Rispiningtati, Rispiningtati; Juwono, Pitojo Tri (Fakultas Teknik, Universitas Brawijaya, 2015)
As a multipurpose dam makes Wonogiri experiencing various problems during operation, the main problem is sedimentation. Therefore the propertly sediment handling is necessary, one of them by doing routine dredging annually. In this study had four alternatives simulation time dredging sediment and dredger addition, further determined that the most effective alternative based on useful life and its economic value. Based on the calculation of sedimentation analysis, economic analysis, and the effectiveness analysis showed that the most feasible alternative is alternative 4, but because it is not profitable for the management of reservoirs, so the recommended alternative is 3, in addition to increasing the useful life of reservoir up to 14.74%, alternative 3 is also more effective economically 10,57% than alternative 1, with the B-C value is Rp. 6.608.820.242.046,-, B/C ratio is 2,79, IRR value is 13,23%, and the B-C value for increased the useful life of reservoir for 5 years is Rp. 1.214.080.491.633,-. Keywords :reservoir sedimentation, sedimentation dredging, economic analysis, effectivenessanalysis, Wonogiri Reservoir